PENGARUH PENGGUNAAN TEPUNG GETAH PEPAYA KONSENTRASI BERBEDA TERHADAP KARAKTERISTIK MUTU KECAP IKAN GABUS (Channa striata) - Prastari, Cindytia; Desmelati, Desmelati; Karnila, Rahman (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
This research was purposed to determine the effect of papaya sap flour additionwith different concentration as catalyst towards snake head (Channa striata) fish saucefermentation. The papaya sap flour contains papain enzym that plays as catalyst duringthe fermentation of snake head fish sauce. The concentration of papaya sap flour usedin this research was 2.5%, 5% and 7.5%. Results shown that the main content ofpapaya sap is protein , around 59.53 %dw. The best concentration of papaya sap flourfor fermenting the snake head fish sauce was 7.5%, with hydrolysis volume 81.33 mland protein amount 88.80 %dw. Total oganoleptic value of gthe fish sauce that wasmade by using 2.5% papaya sap flour was the most favoured by the consumers, thecolor value was 4.52, taste 5.32, textur 5.30, and odor 3.34.